Культурні перехрестя: українська писанка в Канаді в контексті західної естетики - Лесів, М. (Народна творчість та етнографія, 2007)
This article is dedicated to the dominant trends of evolution of the Ukrainian and Canadian pysanka, which the author calls Starokrayeva, National and Ethnical, Popular and Individual paradigms. Besides, the author focuses on aesthetic aspect of pysanka of each paradigm. Research shows either continuation or change in the Ukrainian tradition in different social and cultural contexts, especially due to contact of this tradition with Western culture.